Perbandingan Motivasi Belajar Mahasiswa Semasa Pandemi Covid-19 Melalui Strategi Tugas Terstruktur dan Tugas Mandiri - Syarif Rizalia; Widi Cahya Adi; Maryce Agusthinus Walukou; Jumiati Jumiati (Institut Agama Islam Negeri Kendari, 2022)
This study aims to determine the differences in student learning motivation during the COVID-19 pandemic through the provision of structured assignments and independent assignments. This article is a type of quasi-experimental research. This study's population was all Biology Department students at one of the higher education institutions in Southeast Sulawesi. The sample of this study was 3rd-semester students who programmed the Biology Lesson Planning course, which consisted of two classes, namely Class A (giving structured assignments) and Class B (giving independent assignments), with a total of 27 students in each class. Based on the results of the study, it was found that the analysis of structured task learning motivation (3.37) was lower than the independent task learning motivation (3.54) and the t-count (1.70). Based on the test criteria, it can be said that H0 is rejected because the value of the t-count is greater than the value of the t-table (1.67). It can be concluded that there is a difference in learning motivation between the structured task experimental class and the independent task experimental class.Keywords: Independent assignments, learning motivation; structured assignments